Effects of surface wetness duration, temperature, and inoculum concentration on infection of winter barley by Rhynchosporium secalis - Xue, G.; Hall, R. (Phytoprotection, 1992)
The effects of surface wetness duration, temperature, and inoculum concentration on development of scald in winter barley (Hordeum vulgare) inoculated with race SOI of Rhynchosporium secalisfrom southern Ontario, Canada were examined. On barley line 'GW8614' sprayed with a spore suspension (2 x 105 conidia ml-1), wet periods of 2-48 h and constant temperatures of 10-25°C during the wet and dry periods, 10-25°C during the wet period and 20°C during the dry period, or 20°C during the wet period and 10-30°C during the dry period allowed scald to develop 8.3-11.5 d after inoculation. The disease developed most rapidly and most severely when the wet period after inoculation was 48 h and the temperature of the wet period and subsequent dry period was 20°C. Scald did not develop within 14 d following temperatures of 30°C during the wet period or of 5°C during the wet or dry periods. At inoculum densities of 102-106 conidia ml-1, the disease severity index values (0-100 scale) increased from 53 to 100 in line 'GW8614' and from 0 to 90 in cultivar OAC Acton and the latent periods decreased from 13.3 to 7.8 d in line 'GW8614' and from more than 14 to 8.5 d in cv. OAC Acton. This information should facilitate screening of barley for resistance to scald.